الاستئناف والأثر غير الإيقافي ووقف التنفيذ في القانون الإماراتي: دراسة مقارنة - Ismaeil Ibrahim Husain Ali Alhosani; Dina Imam Supaat; Mahmoud Mohamed Ali Mahmoud Edris (Intelligentia Resources, 2025)
Non-Indexed Publication